The year's best dark fantasy and horror. Volume five - Guran, Paula (PYR, 2024)
This outstanding annual exploration of the year's best dark fiction journeys into the shadows delivers nineteen tales of the haunted, weirdly surreal, evil incarnate, frightening futures, and much more. The Year's Best Dark Fantasy & Horror, Volume 5 includes metaphysical masterpieces from some of today's finest writers of the fantastique. Much like the paranormal, some things need to be experienced to be believed, so delve into these pages and take a delightfully disturbing stroll into the fears that stir us all.